在△ABD和△CBE中,
|
∴△ABD≌△CBE(SAS),
∴AD=CE,∠BAD=∠BCE,
∵∠BCE+∠BEC=90°,∠AEF=∠BEC,
∴∠BAD+∠AEF=90°,
∴∠AFE=90°,
∴AD⊥CE;
(2)(1)中的結(jié)論AD=CE,AD⊥CE仍然成立,理由為:
證明:如圖2所示,
∵∠ABC=∠DBE=90°,
∴∠ABC-∠ABE=∠DBE-∠ABE,即∠ABD=∠CBE,
在△ABD和△CBE中,
|
∴△ABD≌△CBE(SAS),
∴AD=CE,∠BAD=∠BCE,
∵∠BCE+∠BOC=90°,∠AOF=∠BOC,
∴∠BAD+∠AOF=90°,
∴∠AFE=90°,
∴AD⊥CE;
![](http://hiphotos.baidu.com/zhidao/pic/item/9a504fc2d5628535e444649093ef76c6a6ef63de.jpg)
證明:如圖3所示,
∵∠ABC=∠DBE=90°,
∴∠ABC-∠DBC=∠DBE-∠DBC,即∠ABD=∠CBE,
在△ABD和△CBE中,
|
∴△ABD≌△CBE(SAS),
∴AD=CE,∠BAD=∠BCE,
∵∠BAD+∠AMB=90°,∠AMB=∠CMF,
∴∠BCE+∠CMF=90°,
∴∠AFC=90°,
∴AD⊥CE.